A novel group of spindle cell tumors defined by S100 and CD34 co‐expression shows recurrent fusions involving RAF1, BRAF, and NTRK1/2 genes. Issue 12 (1st October 2018) - Suurmeijer, Albert J. H.; Dickson, Brendan C.; Swanson, David; Zhang, Lei; Sung, Yun‐Shao; Cotzia, Paolo; Fletcher, Christopher D. M.; Antonescu, Cristina R.
Abstract: Tumors characterized by co‐expression of S100 and CD34, in the absence of SOX10, remain difficult to classify. Triggered by a few index cases with monomorphic cytomorphology and distinctive stromal and perivascular hyalinization, immunopositivity for S100 and CD34, and RAF1 and NTRK1 fusions, the authors undertook a systematic review of tumors with similar features. Most of the cases selected were previously diagnosed as low‐grade malignant peripheral nerve sheath tumors, while others were deemed unclassified. The tumors were studied with targeted RNA sequencing and/or FISH. A total of 25 cases (15 adults and 10 children) with kinase fusions were identified, including 8 cases involving RAF1, 2 BRAF, 14 NTRK1, and 1 NTRK2 gene rearrangements. Most tumors showed a monomorphic spindle cell proliferation with stromal and perivascular keloidal collagen, in a patternless architecture, with only occasional scattered pleomorphic or multinucleated cells. Most cases showed low cellularity, a low mitotic count, and absence of necrosis. Although a subset showed overlap with lipofibromatosis‐like neural tumors, the study group showed distinctive hyalinization and overt malignant features, such as highly cellular fascicular growth and primitive appearance. All tumors showed co‐expression of S100 and CD34, ranging from focal to diffuse. SOX10 was negative in all cases. NTRK1 immunohistochemistry showed high levels of expression in all tumors with NTRK1 gene rearrangements. H3K27me3 expression performed in a subset of cases was retained. These findings together with the recurrent gene fusions in RAF1, BRAF, and NTRK1/2 kinases suggest a distinct molecular tumor subtype with consistent S100 and CD34 immunoreactivity.